Qualitative Phytochemical Screening of Some Medicinal Plants - P. Suresh; A. Doss; N. Ahamed Kabir (The Bioscan, 2025)
Medicinal plants are abundant in bioactive compounds that are useful in the treatment of a wide range of human illnesses. The phytochemical compounds of these medicinal plants are thought to have medicinal potential. In the present study, qualitative phytochemical screening was conducted on leaf extracts of four medicinal plants - Sphaeranthus indicus, Celosia cristata, Tephrosia purpurea, and Kigelia africana. Solvent extraction was performed using a cold maceration method with ethylacetate, ethanol and aqueous solvents. Qualitative phytochemical analyses were carried out to detect the presence of flavonoids, saponins, tannins, phenolics compounds, coumarins, and quinine Among the extracts, the ethanol extract of S. indicus exhibited the highest number of phytochemicals, while other plants showed the least. The presence of these phytochemicals suggests that these plants possess significant therapeutic potential and may serve as valuable sources for the development of novel plant-based drugs. Traditional medicine, Solvents, Secondary metabolites, Alkaloids